Analysis of the need for ethnopedagogy-based social studies teaching materials at Junior High School 22 Bandar Lampung - Saputra, Bima; Adha, Muhammad Mona; Pujiati, Pujiati (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study addresses the declining awareness of cultural identity among junior high school students, influenced by globalization and intercultural interactions in Lampung. To respond to this issue, the development of ethnopedagogy-based social studies (IPS) teaching materials integrating local wisdom and regional history was proposed. This study aimed to identify the gap between the teaching materials currently used in schools and the proposed teaching materials, as well as to analyze teachers’ and students’ responses toward the development of the product. This research employed a descriptive qualitative approach, with data collected through observations, in-depth interviews, questionnaires, and documentation. The findings revealed significant differences between conventional teaching materials and the ethnopedagogical materials to be developed, particularly in terms of integrating local cultural content. In addition, teachers and students responded positively to the proposed teaching materials. These findings indicate the importance of developing culturally contextualized learning resources to strengthen students’ local knowledge and cultural identity awareness, while supporting the improvement of social studies learning in junior high schools in Lampung.